The Influence of Foreign Direct Investment and Tourism on Carbon Emission in China - Wang, Hong; Xu, Dinghong; Mufarreh Elqahtani, Zainab; Juan, Zhang; Ahmad, Muneeb; Ali, Asad; Khan, Yousaf Ali; Saghir, Amir (Frontiers in Environmental Science, 2022)
The aim of this research is to examine the potential influence of FDI inflows and tourism industry on carbon dioxide emissions in China using System GMM models for a sample period of 1980–2019. Using FMOLS and DOLS models, this research examines the long-term relationship between the variables, as well as the long-term association among components. Co-joining the boards of FMOLS and DOLS models shows a general correlation between the investigation elements and CO2 emissions in China. FDI, tourism sector, and environment-friendly electricity use have all been major contributors to rising CO2 emissions in China for a long time. Using System GMM, FMOLS, and DOLS models in China, we examined the influence of the travel sector on carbon dioxide emissions as well as environment-friendly electricity usage and foreign direct investment. The government of China is being pushed to attract more foreign direct investment in order to improve the system and expand the transportation industry. As a reasonable responsibility to an unnatural climate change, methods for developing the movement business and theories relating to the movement business should be adopted.